Factors associated with pruritic papular eruption of human immunodeficiency virus infection in the antiretroviral therapy era. (April 2014) - Chua, S.L.; Amerson, E.H.; Leslie, K.S.; McCalmont, T.H.; Leboit, P.E.; Martin, J.N.; Bangsberg, D.; Maurer, T.A.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Papular pruritic eruption (PPE) of HIV is common in HIV‐infected populations living in the tropics. PPE is characterized by symmetrically distributed itchy papules, worst on the extremities, with similar microscopic findings to insect bites or stings. What does this study add? Persistent or recurrent PPE in antiretroviral therapy (ART)‐treated persons is associated with greater HIV RNA load at ART commencement but not during treatment. No association was found with CD4 count, CD4 gains and T‐cell activation markers.